MENJADI GURU PROFESIONAL DI ERA DIGITAL - Irma Budiana (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2021)
This research aims to study or study professional teachers in the digital age. This type of research is qualitative. The study of professional teachers in this digital era aims to add insight to teachers and prospective teachers to become professional teachers in the digital era. Being professional means being an expert in your field. But not all experts can be qualified because being qualified is not only an expert problem, but also concerns personality and integrity issues. Being a professional is a unity between integrity and personality combined with his skills. Professional teachers must create a superior school and produce graduates/outputs of quality, great and dignified education. Schools that have educational excellence and success are influenced by the performance of individuals and organizations themselves which include beliefs, cultures, values, and behavioral norms referred to as the human side of organization (human and organizational aspects). Based on the results of the research concluded that (1) professional teachers are teachers who are skilled and experts in carrying out their profession and have received formal recognition based on applicable provisions, both related to their educational background and their position. (2) The digital age is a term often used in the emergence of digital technology or internet networks. This digital era is a time when everyone is technologically literate and all connected, and in this era is a time when all humans can interact and communicate closely even though they are far apart. (3) Being a professional teacher must be qualified and have various competencies relevant to his profession, and have a high motivation to always improve professionalism in order to have competence in accordance with the laws and regulations so as to be able to carry out their duties and obligations in learning / guidance.